2011
DOI: 10.1074/jbc.m111.256701
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Recognition of Triple-helical β-Glucans by an Insect Fungal Receptor

Abstract: The innate ability to detect pathogens is achieved by pattern recognition receptors, which recognize non-self-components such as ␤1,3-glucan. ␤1,3-Glucans form a triple-helical structure stabilized by interchain hydrogen bonds. ␤1,3-Glucan recognition protein (␤GRP)/Gram-negative bacteria-binding protein 3 (GNBP3), one of the pattern recognition receptors, binds to long, structured ␤1,3-glucan to initiate innate immune response. However, binding details and how specificity is achieved in such receptors remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 38 publications
6
68
0
Order By: Relevance
“…In contrast to insoluble linear polysaccharides such as curdlan and cellulose, laminarin is soluble in water, because its ␤-1,6 branches provide an extra degree of freedom by the rotation about the C-5 and C-6 bonds of the glucose ring (39). The crystal structure of N-␤GRP complexed with laminarihexaoses arranged in a triple helical form has shown that N-␤GRP interacts with ␤-1,3-glucans through six glucose residues, two from each laminarihexaose chain (14). Our chemical cross-linking exper- Ten microliters of plasma from day 2 5th instar larvae of M. sexta was incubated with 10 g of N-␤GRP2 with and without 100 g of laminarin, soluble complex, or insoluble aggregate, in wells of a 96-well plate for 1 h at 25°C.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to insoluble linear polysaccharides such as curdlan and cellulose, laminarin is soluble in water, because its ␤-1,6 branches provide an extra degree of freedom by the rotation about the C-5 and C-6 bonds of the glucose ring (39). The crystal structure of N-␤GRP complexed with laminarihexaoses arranged in a triple helical form has shown that N-␤GRP interacts with ␤-1,3-glucans through six glucose residues, two from each laminarihexaose chain (14). Our chemical cross-linking exper- Ten microliters of plasma from day 2 5th instar larvae of M. sexta was incubated with 10 g of N-␤GRP2 with and without 100 g of laminarin, soluble complex, or insoluble aggregate, in wells of a 96-well plate for 1 h at 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…For insect ␤GRP, Kanagawa et al (14) suggested from the crystal structure of N-␤GRP complexed with triple helical laminarihexaoses that an unusually large carbohydrate binding surface on N-␤GRP would enhance its affinity to carbohydrate. We propose that N-␤GRP2 may also employ another strategy in which protein-protein interactions become established as a carbohydrate-protein complex is formed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations